Scale dependence of entrainment‐mixing mechanisms in cumulus clouds. Issue 24 (17th December 2014) - Lu, Chunsong; Liu, Yangang; Niu, Shengjie; Endo, Satoshi
Abstract This work empirically examines the dependence of entrainment‐mixing mechanisms on the averaging scale in cumulus clouds using in situ aircraft observations during the Routine Atmospheric Radiation Measurement Aerial Facility Clouds with Low Optical Water Depths Optical Radiative Observations (RACORO) field campaign. A new measure of homogeneous mixing degree is defined that can encompass all types of mixing mechanisms. Analysis of the dependence of the homogenous mixing degree on the averaging scale shows that, on average, the homogenous mixing degree decreases with increasing averaging scales, suggesting that apparent mixing mechanisms gradually approach from homogeneous mixing to extreme inhomogeneous mixing with increasing scales. The scale dependence can be well quantified by an exponential function, providing first attempt at developing a scale‐dependent parameterization for the entrainment‐mixing mechanism. The influences of three factors on the scale dependence are further examined: droplet‐free filament properties (size and fraction), microphysical properties (mean volume radius and liquid water content of cloud droplet size distributions adjacent to droplet‐free filaments), and relative humidity of entrained dry air. It is found that the decreasing rate of homogeneous mixing degree with increasing averaging scales becomes larger with larger droplet‐free filament size and fraction, larger mean volume radius and liquid water content, or higher relative humidity. The results underscore the necessity and possibility of considering averaging scale in representation of entrainment‐mixing processes in atmospheric models.